Incidence of infrastructure on the satisfaction of customers and sellers of the Municipal Market of Agricultural Producers of San Pedro de Riobamba (EMMPA). - Arboleda Alvarez, Luis Fernando (2016)
Research presented as objective, proposing a plan for improvement of the infrastructure of the Municipal Market of Agricultural Producers San Pedro de Riobamba (EMMPA), detecting the main problem market infrastructure affects the satisfaction of customers and vendors, demonstrating the following hypothesis: the market infrastructure of agricultural producers San Pedro de Riobamba affects customer satisfaction and sellers. To design the plan a baseline from the requirements for markets as Ecuadorian Technical Standard Ecuadorian Institute of Standardization (NTE INEN 2687: 2013) rose and the percentage of compliance with the requirements determined, then an instrument was developed which allowed to measure customer satisfaction and sellers, depending on the infrastructure for marketing of products obtaining reliability by alpha Cronbach, the Exploratory Factor Analysis (AFE) (KMO = 0.881) was developed in order to determine the construct validity. It was found that there is a close relationship between the seller significant / producer and seller / producer EMMPA for marketing their products (r = 0.812, p <0.05) constructs infrastructure satisfaction.